An Experimental Study of Strength Increase in Masonry Wall Reinforced by One-sided Khorasan Mortar with Steel Mesh - Volkan Öztaş; Necdet Torunbalcı (Civil Engineering Journal, 2023)
The strengthening of masonry structures is of paramount importance due to their inherent lack of tensile elements, rendering them susceptible to tensile stresses induced by horizontal loads and the resultant substantial damage. Consequently, this study aims to develop a reinforcement system for the strengthening of historical masonry structures by using mortars devoid of cement and modern pozzolan. Experiments were conducted on masonry walls unreinforced and reinforced by a one-sided Khorasan mortar with steel mesh. Initially, six masonry brick walls constructed using Khorasan lime mortar were prepared. Subsequently, after a waiting period of six months, Khorasan plaster mortar, reinforced with steel mesh, was applied to three masonry walls on one side. Following an 18-month waiting period, all samples were subjected to testing in an experimental setup designed and manufactured for this purpose. The wall reinforcement resulted in a significant increase, with the average peak load by 215.73%, and the average displacement by 48.82%. The experimental shear force on unreinforced walls was found to be 41.23% lower than Eurocode-6 and 1.41% lower than TBDY-2018. In the case of one-sided reinforced walls, the experimental shear force was 9.94% lower than Eurocode-6 and 6.16% lower than TBDY-2018. This form of strengthening not only obviates the use of potentially damaging cement in historical buildings but also extends the lifespan of the reinforced structures. Doi: 10.28991/CEJ-2023-09-12-019 Full Text: PDF